A 4 bp InDel in the Promoter of Wheat Gene TaAFP-B Affecting Seed Dormancy Confirmed in Transgenic Rice - Feng, Yumei; Han, Yang; Han, Bing; Zhao, Yongying; Yang, Yan; Xing, Yanping (Frontiers in Plant Science, 2022)
Background Wheat (Triticum aestivum L.) ABA insensitive five (ABI5) gene (TaAFP) is a homologue of the ABI5 binding protein (AFP) gene of Arabidopsis thaliana. It is well documented that AtAFP is a negative regulator in ABA signaling and regulates embryo germination and seed dormancy. Previously, TaABI5 was found to be expressed specifically in seed and accumulated during wheat grain maturation and dormancy acquisition, playing an important role in seed dormancy. In a previous study, we identified two allelic variants of TaAFP on chromosome 2BS in common wheat, designated as TaAFP-B1a and TaAFP-B1b, respectively. Sequence analysis revealed a 4-bp insertion in the promoter of TaAFP-B1a compared with TaAFP-B1b, which affected the mRNA transcription level, mRNA stability, translation levels of GUS, and tdTomatoER and GUS activities, determining seed dormancy in common wheat. Results The transcription and translation levels of TaAFP-B were significantly reduced in ProUbi-TaAFP-BaS transgenic plants compared with ProUbi-TaAFP-BbS. The average GI (germination index) values of TaAFP-BaS was significantly lower than those of TaAFP-BbS in T1 and T2 transgenic rice seeds, whereas mature TaAFP-BaS transgenic seeds exhibited increased ABA sensitivity and higher content of endogenous ABA compared with TaAFP-BbS. Conclusion: The 4-bp insertion in the promoter of TaAFP-Ba decreased the transcript abundance and translation level in transgenic rice. This insertion increased sensitivity to ABA and content of endogenous ABA in mature seeds, leading to a higher capacity of seed dormancy and pre-harvest sprouting tolerance in transgenic rice.